2019
DOI: 10.2196/13793
|View full text |Cite
|
Sign up to set email alerts
|

A Mobile Phone App Featuring Cue Exposure Therapy As Aftercare for Alcohol Use Disorders: An Investigator-Blinded Randomized Controlled Trial

Abstract: Background Cue exposure therapy (CET) is a psychological approach developed to prepare individuals with alcohol use disorder (AUD) for confronting alcohol and associated stimuli in real life. CET has shown promise when treating AUD in group sessions, but it is unknown whether progressing from group sessions to using a mobile phone app is an effective delivery pathway. Objective The objectives of this study were to investigate (1) whether CET as aftercar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 57 publications
0
18
1
2
Order By: Relevance
“…Of the seven apps for use among individuals with AUD there have been three RCTs. One found a significant reduction in 'risky drinking days' among participants using an app compared to controls given only treatment as usual (P = 0.003) [25], while the other two trials found no significant differences in any alcohol consumption outcomes between the intervention and control groups [29,32]. The other four trials in this population had mixed results, with three finding significant reductions in alcohol consumption measures and one finding no significant changes.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Of the seven apps for use among individuals with AUD there have been three RCTs. One found a significant reduction in 'risky drinking days' among participants using an app compared to controls given only treatment as usual (P = 0.003) [25], while the other two trials found no significant differences in any alcohol consumption outcomes between the intervention and control groups [29,32]. The other four trials in this population had mixed results, with three finding significant reductions in alcohol consumption measures and one finding no significant changes.…”
Section: Resultsmentioning
confidence: 92%
“…Of the 19 unique apps, seven were designed for use among youth [14][15][16][17][18][19][20][21] and 12 in adult populations [22][23][24][25][26][27][28][29][30][31][32][33][34]. The results of these studies are summarised in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 25 studies, 14/25 (56%) used an mHealth app, 4/25 (16%) used telephone or interactive voice response, 3/25 (12%) used mHealth serious games or cognitive training delivered on mobile devices, and four studies used either mHealth SMS or mHealth + telephone (2/26 each, 8%). Of the 25 studies analyzed over a 10-year period, 2 were from 2012 [ 17 , 18 ], 1 was from 2013 [ 19 ], 2 were from 2014 [ 20 , 21 ], 1 was from 2015 [ 22 ], 3 were from 2016 [ 23 , 24 , 25 ], 4 were from 2017 [ 26 , 27 , 28 , 29 ], 2 were from 2019 [ 30 , 31 ], and 2020 [ 32 , 33 ], 4 were from 2021 [ 34 , 35 , 36 , 37 ], and 2022 [ 38 , 39 , 40 , 41 ]. Zero studies were from 2018.…”
Section: Resultsmentioning
confidence: 99%
“…The study will utilize a parallel randomized controlled trial design including 2 groups (Aware treatment only versus Soberlink plus Aware treatment), in which the Aware treatment only group will act as an active control group (a further detailed explanation of the groups is described below). The block randomization sequence will allow for equal representation between the 2 groups without bias on gender, age, or ethnicity, given that all individuals will be categorized as a single variable [ 27 ]. The intervention for both groups will last for 3 months with a 6-week follow-up, during which each participant will be interviewed at admission (T1), 1 month in (T2), 2 months in (T3), 3 months in (T4), and follow-up (T5), as seen in Figure 1 [ 28 ].…”
Section: Methodsmentioning
confidence: 99%